The effect of an air purifier on aerosol generation measurements during clinical motility testing. Issue 4 (2nd August 2021) - Verbeure, Wout; Geeraerts, Annelies; Huang, I‐Hsuan; Timmermans, Lien; Tóth, Joran; Geysen, Hannelore; Cools, Louise; Carbone, Florencia; Schol, Jolien; Devriese, Herman; Haesaerts, Rico; Mori, Hideki; et al.
Abstract: Background: Aerosol spread is key to interpret the risk of viral contamination during clinical procedures such as esophageal high‐resolution manometry (HRM). Installing an air purifier seems a legitimate strategy, but this has recently been questioned. Methods: Patients undergoing an HRM procedure at the Leuven University Hospital were included in this clinical study. All subjects had to wear a surgical mask which was only lowered beneath the nose during the placement and removal of the nasogastric catheter. The number of aerosol particles was measured by a Lasair ® II Particle Counter to obtain data about different particles sizes: 0.3; 0.5; 1.0; 3.0; 5.0; and 10.0 µm. Measurements were done immediately before the placement and the removal of the HRM catheter, and one and 5 min after. A portable air purifier with high‐efficiency particle air filters was installed in the hospital room. Key Results: Thirteen patients underwent a manometry examination. The amount of 0.3 µm‐sized particles was unaffected during the whole procedure. The larger particle sizes (1.0; 3.0; 5.0; and 10.0 µm) decreased when the catheter was positioned, but not 0.5 µm. During the HRM measurements itself, these numbers decreased further. Yet, 1 min after catheter removal a significant elevation of particles was seen, which did not recover within 5 min. Conclusions & Interferences: Based on this study, there is no evidence that filtration systems reduce aerosol particles properly during a clinical investigation.